2020
DOI: 10.1007/978-3-030-32357-8_133
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic Drops with Two- and Three-Body Interactions Close to the Unitary Limit

Abstract: When the binding energy of a two-body system goes to zero the two-body system shows a continuous scaling invariance governed by the large value of the scattering length. In the case of three identical bosons, the three-body system in the same limit shows the Efimov effect and the scale invariance is broken to a discrete scale invariance. As the number of bosons increases correlations appear between the binding energy of the few-and many-body systems. We discuss some of them as the relation between the saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This research follows other studies that can be found in Refs. [42][43][44][45]. In the present study we perform a step further constructing a gaussian characterization of the unitary window for different observables in the three-body sector.…”
Section: Discussionmentioning
confidence: 99%
“…This research follows other studies that can be found in Refs. [42][43][44][45]. In the present study we perform a step further constructing a gaussian characterization of the unitary window for different observables in the three-body sector.…”
Section: Discussionmentioning
confidence: 99%